Clinical Phenotype and Genetic Analysis of Twins With Congenital Coagulation Factor V Deficiency. Issue 2 (March 2022) - Wei, Yanhui; He, Yuzhuo; Guo, Xuejun
Abstract : Objective: The aim was to investigate the clinical characteristics and molecular pathogenic mechanism of twins with congenital factor V (FV) deficiency. Methods: We comprehensively analyzed the clinical manifestations and laboratory test results of a set of twins and their parents and performed point mutation analysis with direct high-throughput exon sequencing. Results: The prothrombin time and activated partial thromboplastin time were prolonged for both probands, and the FV activity levels were 13.0% and 9.8%. Next-generation sequencing showed that the affected individuals harbored a paternal c.5113A>C (p.S1705R) and a maternal c.4949C>T (p.A1650V) heterozygous variants in the FV gene, which conformed to an autosomal recessive inheritance pattern. This is the first report of these point mutations. The older boy also had a congenital patent foramen ovale. Conclusion: In this set of twins, missense mutations of the FV gene were related to congenital FV deficiency but unrelated to the patent foramen ovale observed in the older boy.